Dendrobine biosynthesis in Dendrobium nobile in four different habitats is affected by the variations in the endophytic fungal community - Li, Lin; Liu, Chaobo; Wen, Wei’e; Li, Qingqing; Pan, Tiantian; Li, Zhaogao; Qian, Gang; He, Yuqi; Xu, Delin (Frontiers in Microbiology, 2022)
Dendrobium nobile, an epiphytic plant, is a traditional medicinal herb with abundant endophytes. It is unclear whether the variation in the diversity and abundance of endophytes could stimulate the biosynthesis of medicinal compounds in the plant. In this study, we collected fresh stems of D. nobile from four habitats for investigating the fungal community structure, dendrobine content, and environment factors and their correlations. The results indicated no significant difference in endophytic fungal diversity among the habitats; however, different dominant or special endophytic genera were observed in the hosts from different habitats. The altitude was observed to be positively related to the dendrobine content, as the stems collected from the altitude of 692 m exhibited the highest level of dendrobine. Furthermore, the relative abundance of Toxicocladosporium was found to be positively correlated with the altitude and dendrobine content. The epiphytic matrix exhibited a significant negative correlation with the relative abundance of the endophytic fungus Gibberella but did not exhibit any significant correlation with the dendrobine content. The results indicated that the abundance of endophytes in D. nobile was affected by the altitude and epiphytic matrix and that high Toxicocladosporium abundance and high altitude were conducive to dendrobine production.